Thursday

November 27, 2014

November 27, 2014

Posted by **Anonymous** on Friday, July 19, 2013 at 7:34pm.

f '(x) = 3ex - 4x; f(0) = 10

f(x) =

- Calculus -
**Chol**, Friday, July 19, 2013 at 8:36pmf(x) = 3e^x -2x^2 + c

10 = 3e^0 -2(0)^2+ c

10 =3-0+ c

7= c

F(x) = 3e^x -2x^2 + 7

**Answer this Question**

**Related Questions**

Calculus - Find f (x) by solving the initial value problem. f '(x) = 6x^2 - 10x...

math - What strategy did you use in solving this problem? 22. Suppose that you ...

calculus - find the solution of the initial value problem y'=xye^x; y(1)=1

calculus - Please help find the solution to the initial value problem dy/dx=(1+...

Calculus - For solving initial value problems is there any way to do it without ...

Calculus - Show that y= x + sinx-pi satisfies the initial value problem dy/dx=1...

Calculus - I'm having trouble with part of a question in a problem set. The ...

calculus - A quantity has the value P at time t seconds and is decreasing at a ...

calculus - A quantity has the value P at time t seconds and is decreasing at a ...

Calculus - I am having trouble solving this problem: "Find where the tangent ...